Factors Influencing Church Membership Retention in Catholic Church: A Case Study of Catholic Diocese of Aguleri in Nigeria. - Amuluche, Simeon Chukwuma; Pariyaprasert, Witsaroot (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2024)
This research proposed to investigate factors influencing Church Membership Retention within the Catholic Diocese of Aguleri in Nigeria. It provides a comprehensive review of literature on six key independent variables central to the study, including, Church Commitment, Church Spirituality, Transformational Leadership, Culture, Church Evangelism, and Church Programs, with the dependent variable being Church Membership Retention. The research objectives were as follows: 1) to assess whether Church Commitment, Church Spirituality, Transformational Leadership, Culture, Church Program, and Church Evangelism serve as predictors for Church Membership Retention in the Catholic Diocese of Aguleri; 2) to examine the degree of impact among Church Commitment, Church Spirituality, Transformational Leadership, Culture, Church Program, Church Evangelism, and Church Membership Retention; 3) to provide valuable information about the model and variables to various stakeholders. This research employs a quantitative approach and questionnaire was developed via google form and 400 valid respondents’ answers were analyzed through JAMOVI software. This research applied Cronbach’s Alpha, Descriptive and Inferential Statistics to evaluate the reliability of the questionnaire, analyze demographic information and testing the hypotheses. The research findings indicated that Church Commitment, Church Spirituality, Church Programs, and Church Evangelism have significant effects on Church Membership Retention. However, Transformational Leadership and Culture show no significant effects on Church Membership Retention. Human capital is very vital for successful growth, sustainability and life of the Church. The study underscores the interconnectedness of factors influencing members’ decisions to remain within the church community, providing insights for informed decision by church leaders and practitioners to enhance retention strategies.